STRATEGIES FOR INTRODUCING SCIENCE MUSEUMS IN UZBEKISTAN - Fazilova Dilrabo Xudaykulovna (Uzbekistan Open Conference, 2026)
This article analyzes strategic approaches to establishing and developing science museums in Uzbekistan. It highlights the role of science museums in increasing young people's interest in science, promoting STEM education, fostering innovative thinking, and developing informal learning environments. The study examines organizational, pedagogical, and technological mechanisms for creating science museums based on international experience, as well as methods for integrating them with educational institutions and research centers.
Keywords: science museums; Uzbekistan; STEM education; informal learning; innovative thinking; science popularization; interactive exhibitions; museum pedagogy; scientific and educational infrastructure; youth